Feasibility Study of Moringa and Pandan Wangi Coconut Farm at PT. Bali Agro Investama Penyaringan Plantation Unit, Jembrana - Putu Sri Adnyasari; I GAA Ambarawati; I Wayan Budiasa (JURNAL MANAJEMEN AGRIBISNIS, 2021)
Bali Agro Investama, the filtering plantation unit, Jembrana, is one of the ones that has high potential in the development of Moringa and fragrant pandan coconut. This study aims to (1) analyze the feasibility of moringa and coconut farming at PT. Bali Agro Investama; (2) To analyze the feasibility of moringa and coconut farming at PT. Bali Agro Investama. The data used are primary data and secondary data. Designed with descriptive analysis and business feasibility analysis using investment criteria, namely NPV (Net Present Value (NPV)), IRR (Internal Rate of Return (IRR)), Net Benefit-Cost Ratio (Net B/C), payback period, and analysis sensitivity. Data were collected through in-depth interviews, observation, documentation, and literature study. There are two variables in this study, namely the benefits and costs variables. The results of research on non-financial aspects where this company meets five aspects, namely legal aspects, marketing aspects, management aspects, and technical aspects. Business feasibility analysis using investment criteria obtained the following results (1) NPV > 0 (2) IRR > 1%. (3) Net B/C > 1. (4) Payback period without bank financing is 6.85 years and with bank financing is 7.52 years. Based on the results of sensitivity analysis, this project is sensitive to changes in operating costs and changes in revenue. From the results of this study it can be concluded that the farming of Moringa and Pandan Fragrant Coconut at PT. BAI deserves to be run. The results of this study are expected to be a reference for those in need